Sewage sludge levels on the development and nutrition of sunflower plants - Figueiredo Lobo, Thomaz [UNESP] (2009)
This study aimed to evaluate the effect of substituting chemical nitrogen (N) fertilization for equivalent N levels from sewage sludge of Wastewater Treatment Plant (WTP) on sunflower plant development. Nutrient levels in physiologically mature leaves and seeds, besides nutrient exportation during a 130-day assay, were also assessed. The experiment was carried out in 100 m2 permanent plots at São Manuel Farm, which belongs to School of Agronomical Sciences, São Paulo State University- UNESP, Botucatu, São Paulo State, Brazil. The farm is located in the municipality of São Manuel, São Paulo State. Experimental design was in randomized blocks including 5 treatments and 5 replicates. Treatments were: T1 - chemical N fertilization according to the recommendation for the culture; T2 - 50% N from sewage sludge and 50% N from chemical fertilization; T3 - 100% N from sewage sludge; T4 - 150% N from sewage sludge; T5 - 200% N from sewage sludge. For all treatments, equal amounts of P and K fertilization were applied. Treatments differed for plant height from 21 to 64 days, stem diameter from 28 to 57 days, and leaf number from 21 to 38 days. Seed nutrient levels slightly varied; however, the quantities of exported N, P, Mg, Fe and Zn varied as sewage sludge levels increased.